Inserción en la economía global, comercio exterior y geo-economía: los Tratados de Libre Comercio México-Centroamérica - Soto Acosta, Willy (2013)
The paper examines the renegotiation of bilateral free trade agreements between the Central American countries and Mexico in a “new” common to the participating States.It analyzes the process geo-economicand international political context behind this renegotiation.The articles examines how the figure of FTA allows states inserted intothe global economy and to address theemerging threats of global risk society.It also presents a reflection on the economic growth and income distributionin regional integration schemes.